Personality Competence of Counselors in Guidance and Counseling Services at Junior High Schools in Magelang - Lianasari, Dewi; Purwati, Purwati (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2022)
The success of the implementation of guidance and counseling services in schools is determined by one of the personality competencies possessed by the counselor. Personal competency standards are one part of the counselor competency standards. Counselor competency standards are minimum standards that must be known, achieved and performed proficiently by counselors. The purpose of this study was to produce an instrument in the form of a counselor personality competency scale. This study uses a Research and Development design up to the product trial stage on a limited basis. The data collection instrument used a personality competency scale. The results showed that using the personality competency scale that had been tested, it was seen that 97% were in the medium category and 3% were in the high category.